(untitled) (Journal of National Institute of Ophthalmology, 2023)
Introduction: Strabismus is a misalignment caused by abnormalities in binocular vision or by anomalies of neuromuscular control of ocular motility. Both children and adults may present with strabismus in the health care center for management. Proper choice of management plan can provide satisfaction to the patients. The aim of surgical management is to optimize the best corrected visual acuity (BCVA) of both eyes, maintain normal binocular fusion and improve cosmesis. Purpose: To review the scientific literature that evaluates the prognostic factors for successful outcome of horizontal strabismus surgery in pediatric group. Methods: The relevant articles are collected and reviewed from Google scholar, PubMed web search and published national and international journals. Our main focus is to concentrate about factors of successful strabismus surgery for pediatric group. Results: This review shows that factors affecting surgical and cosmetic outcome of squint surgery are related to age of presentation, gender distribution, pattern of laterality, types of squint- alternate / unilateral, Pre-operative deviation, binocular vision, association of refractive error etc. This resultant workable framework further helps to evaluate and take proper decision regarding management of these patients for better successful outcome. Conclusion: Proper preoperative assessment followed by proper choice of surgical options leads to surgical success. Effective surgical options coupled with effective post-surgical rehabilitation will provide the best outcome for such strabismus surgery. J.Natl.Inst.Ophthalmol.2023;6(1): 48-53